PENGARUH SENAM IRAMA CERIA TERHADAP KEMAMPUAN GERAK DASAR PESERTA DIDIK TUNAGRAHITA SLB KINASIH PONTIANAK - Holijah, Rizki Nur; Supriatna, Eka; Hidasari, Fitriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem that occurs in this study is the slowness of motoric skills that occur in mentally retarded children. The form of the study used is a pre-experimental design using one-group pretest-posttest design. The data collection tool is in the form of an assessment sheet with the number of 5 tests submitted. Based on the results of data analysis obtained, the average pretest value is 88.25 and the average posttest value is 111.25 with a 26% increase. With the calculation of the pretest normality test results on sig. (4.34)> Î± (0.05) and posttest on sig. (4.79)> Î± (0.05), so that the pretest and posttest data are normally distributed. The calculation of homogeneity test with pretest and posttest results on sig. (1,09)> Î± (0,05) is said that the variant of two or more data population groups is the same. Then the result of the sig t-test. 28.22> 2.35336 which indicates that Ho is rejected and Ha is accepted means that it can be concluded that there is an effect of joyful rhythmic gymnastics on the basic motion cability of students with mental impairments at SLB Kinasih in Pontianak city before and after being given treatments.Â Keywords: Basic Motion Capability, Mentally Impaired, Rhythmic Gymnastics